A Causal Relationship Between Selective Economic Growth Determinants In Pakistan (A Causality Analysis) - Munawar Jan,; Himayatullah Khan, (Dialogue Social Science Review (DSSR), 2025)
This research paper aims to explore the causal relationship between economic growth determinants in Pakistan during the study period from 1990-2021. For this purpose, log linear regression model was analyzed. For analysis purpose descriptive statistics analysis, correlation analysis, and Pair-wise Granger Causality test has been utilized. Pair-wise Granger Causality test of economic growth model indicates that one-way causality exists between GDP and foreign remittance; GDP and imports; FDI inflows and inflation; FDI inflows and exports; foreign remittance and exports; foreign remittance and imports; exports and imports; exports and labour force participation rate; interest rate and exports; labour force participation rate and imports; interest rate and imports; and labour force participation rate and interest rate. While bidirectional causality exists between labour force participation rate and GDP. Keywords: FDI Inflows, Economic Growth, Correlation, Pair-wise Granger Causality, and Pakistan.